PENGARUH MODEL PEMBELAJARAN TGT BERBASIS LKPD TERHADAP PEMAHAMAN KONSEP MATEMATIKA KELAS V SDN SUCI 1 - Muhamad Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the cooperative learning on fifth-grade students' conceptual understanding of mathematics at SDN Suci 1. The background of the study stems from low student learning outcomes and limited active participation in the learning process, especially in mathematics. This research employs a pre-experimental method with a one-group pretest-posttest design. The research subjects consist of 28 fifth-grade students. The instrument used is a written test that measures higher-order thinking skills (C4 – analyzing and C6 – creating). The results show a significant improvement in students' conceptual understanding after implementing the TGT model with LKPD. Thus, the TGT model based on LKPD is proven effective in enhancing students’ mathematical conceptual understanding and can serve as an alternative learning strategy at the elementary school level.